2022
DOI: 10.1109/tbme.2022.3163429
|View full text |Cite
|
Sign up to set email alerts
|

Deep Multi-Branch Two-Stage Regression Network for Accurate Energy Expenditure Estimation With ECG and IMU Data

Abstract: Objective: Energy Expenditure (EE) estimation plays an important role in objectively evaluating physical activity and its impact on human health. EE during activity can be affected by many factors, including activity intensity, individual physical and physiological characteristics, environment, etc. However, current studies only use very limited information, such as heart rate and step count, to estimate EE, which leads to a low estimation accuracy. Methods: In this study, we proposed a deep multibranch two-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…The complex and diverse factors that affected EE make real-time and accurate estimation challenging, particularly for prediction tasks involving different populations. 22 , 23 In this study, we observed that the single ML algorithm did not achieve satisfactory overall prediction results, including NN algorithms with nonlinear approximation capabilities (R 2 = 0.90; Figure 1 C). A potential explanation is that the strong correlation relationship between the factors and EE in a single population disappears or is neutralized in most samples.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…The complex and diverse factors that affected EE make real-time and accurate estimation challenging, particularly for prediction tasks involving different populations. 22 , 23 In this study, we observed that the single ML algorithm did not achieve satisfactory overall prediction results, including NN algorithms with nonlinear approximation capabilities (R 2 = 0.90; Figure 1 C). A potential explanation is that the strong correlation relationship between the factors and EE in a single population disappears or is neutralized in most samples.…”
Section: Discussionmentioning
confidence: 71%
“…Developing prediction models with broad applicability and high accuracy for walking EE is challenging because of the complex time-varying and nonlinear nature of the human body, the complex and diverse factors affecting EE, and the different prediction factors and function relationships among different populations. 22 , 23 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their results showed lower RMSE values with the CNN model (1.12 kcal/min) compared to the ANN model (1.73 kcal/min). Ni et al [ 55 ] estimated EE in adults from the electrocardiogram (ECG) and inertial measurement unit (IMU) using a deep multibranch two-stage regression network (DMTRN) model during the Bruce treadmill test, carried out until exhaustion. Their results showed a close correlation between the estimated EE and the reference EE measured by an indirect calorimeter (R 2 = 0.97, RMSE = 0.71 kcal/min).…”
Section: Discussionmentioning
confidence: 99%
“…Ni et al [ 18 ] developed a deep multi-branch two-stage regression network (DMTRN) energy expenditure (EE) estimation. The proposed approach is mainly used to predict the accurate EE which produces necessary information for healthcare centers.…”
Section: Related Workmentioning
confidence: 99%